Maternity Leave and Gender Equality: Comparative Studies of Indonesia, Malaysia, and Thailand - Viola D. Oceanio (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
This article discusses the implications of maternity leave on gender equality by taking comparative cases in Indonesia, Malaysia, and Thailand. This article focuses on three important issues, namely the implementation of maternity leave policies, the funding system for maternity leave policies, and the implications of these policies on gender equality in the workplace. This article uses secondary data from official government documents, and documents from international institutions, such as International Labor Organization, World Bank, Asian Development Bank, and related studies. The results of the study show that maternity leave in Indonesia, Malaysia, and Thailand complies with the recommendations of the International Labor Organization conventions 1952 and 2000. The benefits provided by maternity leave accommodate women to work and take care of children. In funding maternity leave, Indonesia and Malaysia use the employer liability scheme, while Thailand uses a combination of employer liability and the social security act. These funding schemes are aimed at employees in the private and informal sectors. To promote gender equality in the workplace, the benefits of maternity leave are influential in this effort. The more companies adopt this family-friendly work environment, the more it encourages enhancing gender equality in the workplace. The study finds women are barely in managerial positions due to their responsibility in the family matter. The discussion of maternity leave in Indonesia, Malaysia, and Thailand cases leads to a better understanding of the implementation of maternity leave in developing countries, for which there is currently a research gap.